How do you solve -11t + 8( 2t - 6) = 2?

1 Answer
Jul 6, 2017

t = 10

Explanation:

In order to solve this, you need to expand 8(2t-6) first. Expanding this, you will get 16t - 48.

Replacing 8(2t-6) with what we just got, we will get: -11t + 16t - 48 = 2.

We can combine -11t with 16t, i.e. -11t + 16t = 5t, which will result in a 5t.

Writing out the equation again with our new computation included, we will get: 5t - 48 = 2.

Then we need to get rid of the constant -48 so we add 48 to both sides and we will end up with 5t = 50. Divide both sides by five and t = 10.

If we plug in 10 for t, we should get 2.